The Philosophy of Organizational Forgetting In Frame of Learning and Organizational knowledge - ابراهيم, ابراهيم خليل (Journal of Economics and Administrative Sciences, 2015)
current research aims to build an intellectual framework for concept of organizational forgetting, which is considered one of the most important topics in contemporary management thought, which is gain the consideration of most scholars and researchers in field of organizational behavior, which is to be a loss of intentional or unintentional knowledge of any organizational level. It turned out that just as organizations should learn and acquire knowledge, they must also forget, especially knowledge obsolete and worn out. And represented the research problem in the absence of Arab research dealing with organizational forgetting, and highlights the supporting infrastructure core, and show a close relationship with organizational learning and knowledge, and thus contributing to the embodiment of its contents in our organizations Arabic, which is the latest gap caused the omission of one of the vital topics in the field of organization theory and organizational behavior. And then rising of necessity to exploring the hidden aspects of the topic, to The review search method adopted in the methodology through the analysis of the relevant literature through three chapters, the research found a set of conclusions and recommendations that can help the Arab Director in the adoption of this concept and considered it as business philosophy in managing of his organization